The ideal life;: addresses hitherto unpublished - Drummond, Henry (Dodd, Mead and company, 1913)
Ill-temper.--Why Christ must depart.--Going to the Father.--The eccentricity of religion.--"To me to live is Christ."--Clairvoyance.--The three facts of sin.--The three facts of salvation.--"What is your life?"--Marvel not.--The man after God's own heart.--Penitence.--What is God's will?--The relation of the will of God to sanctification.--How to know the will of God.